Is steel wire closure of sternotomy better than polyester suture closure?. (May 2014) - Malhotra, Amber; Garg, Pankaj; Bishnoi, Arvind Kumar; Pendro, Varun; Sharma, Pranav; Upadhyay, Madhav; Gandhi, Sanjay
Introduction: Median sternotomy is the preferred approach for open heart surgeries. The sternotomy incision is predominantly closed with either steel wire or polyester suture. The type of material used is primarily based on the surgeon's choice, and both materials achieve a good result. No prospective clinical study has been undertaken to evaluate differences in the incidence of wound infection and the degree of pain associated with both techniques. Patients and methods: Our randomized controlled double-blind study included 200 adults undergoing single-valve replacement. The technique of surgery, apart from the material used for sternal closure, was the same in both groups. Postoperatively, patients were analyzed for wound infection and wound pain based on the ASEPSIS score and Numeric Pain Rating Score, respectively. Results: The polyester suture group had a significantly higher mean ASEPSIS score, indicating a higher incidence of wound infection, and more late wound complications. The polyester suture group also had a significantly higher mean pain score. The steel wire group had significantly higher mediastinal drain output in the first 48 h after surgery. Conclusion: The use of polyester suture for sternal closure in adult patients results in increased wound infection, wound pain, and late wound complications, but lower mediastinal drain output.